Viewing Mothers with Consumption of Katuk Leaf Extract (Sauropus Androgynus) on Hemoglobin Increase in Digesting Mothers at Rianti Amd.Keb Clinic Tanjung Beringin Year 2025 - Nitasya, Qory; Sihombing, Setia; Dewiwati, Tri Suci; Pinem, Devi Susana (Jurnal EduHealth, 2025)
Postpartum anemia often occurs due to blood loss during labor, lack of iron intake, as well as increased nutritional needs during the breastfeeding period. Recent data from the Indonesian Ministry of Health (2023) shows that 38.5% of postpartum women experience mild to moderate anemia. One of the non-pharmacological efforts to overcome anemia in nursing mothers is katuk leaves (Sauropus androgynus) as a breast milk facilitating plant, but also contains iron, vitamin C, and other active compounds that are beneficial for increasing hemoglobin levels (Widowati et al., 2021).The purpose of the study was to be able to carry out midwifery care in nursing mothers with consumption of katuk leaf extract (sauropus androgynus) to increase hemoglobin in nursing mothers at the Rianti Amd.Keb Tanjung Beringin Clinic in 2025 using the Varney 7-step midwifery approach. The research method is descriptive method. From the case study of Mrs. S evaluation by giving consumption of katuk leaf tea extract (sauropus androgynus) to increase hemoglobin in nursing mothers can be concluded with treatment for 2 weeks with 3 visits obtained HB 12 gr / dL and conjunctiva is no longer pale.